2018
DOI: 10.3389/fendo.2018.00691
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Circulating Netrin-1 Concentration, Impaired Fasting Glucose, and Newly Diagnosed Type 2 Diabetes

Abstract: Background: The protein netrin-1 has demonstrated anti-inflammatory, tissue regeneration, and immune modulation properties. Although inflammation is a major contributing factor in the development of insulin resistance and type 2 diabetes, little is known about a possible relationship between serum netrin-1 and type 2 diabetes. Therefore, we investigated the association between circulating levels of netrin-1 and glycometabolic parameters predictive of type 2 diabetes.Methods: Serum samples were collected from 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 47 publications
(54 reference statements)
3
24
2
1
Order By: Relevance
“…Liu, et al reported that plasma Netrin‐1 levels were lower in newly diagnosed type 2 diabetes mellitus patients than those in healthy controls and also the levels were negatively correlated with blood glucose levels and insulin resistance. Conversely, increased serum Netrin‐1 concentrations in patients with type 2 diabetes have been reported in recent studies . Our results demonstrated decreased serum Netrin‐1 and Unc5b levels in periodontitis patients and also the levels were negatively correlated with the whole mouth inflammatory clinical parameters.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Liu, et al reported that plasma Netrin‐1 levels were lower in newly diagnosed type 2 diabetes mellitus patients than those in healthy controls and also the levels were negatively correlated with blood glucose levels and insulin resistance. Conversely, increased serum Netrin‐1 concentrations in patients with type 2 diabetes have been reported in recent studies . Our results demonstrated decreased serum Netrin‐1 and Unc5b levels in periodontitis patients and also the levels were negatively correlated with the whole mouth inflammatory clinical parameters.…”
Section: Discussionsupporting
confidence: 66%
“…Conversely, increased serum Netrin-1 concentrations in patients with type 2 diabetes have been reported in recent studies. 32,33 Our results demonstrated decreased serum Netrin-1…”
Section: Discussionmentioning
confidence: 51%
“…Esse possível aumento pode estar relacionado à maior frequência de fatores de risco cardiovasculares neste grupo no presente estudo, fatores que podem levar a um aumento dos níveis de marcadores inflamatórios. 36 No entanto, mesmo após o ajuste desses fatores, níveis elevados de Netrina 1 e IL-1β permaneceram associados a pior prognóstico, demonstrando que esses marcadores inflamatórios estão independentemente associados a pior prognóstico e podem estar relacionados à redução da capacidade arterial já observada em mulheres idosas, quando comparados aos homens.…”
Section: Discussionunclassified
“…The anti-oxidant factors were previously reported in the context of DKD, although mainly in functional or small cross-sectional studies [49][50][51][52][53] . In addition, investigation of other protective factors in diabetes patients, such as growth factors, adenosine, immune proteins, fibroblast growth factor receptors and netrins, is in early stages [54][55][56][57][58][59][60][61] .…”
Section: Human Studies Of Protective Factors For Renal Function Lossmentioning
confidence: 99%